Effect of grain size and distribution on the corrosion behavior of Y2O3 dispersion-strengthened 304 stainless steel. (June 2022) - Zhang, Wenjun; Liu, Fenggang; Liu, Lixin; Li, Qiuge; Liu, Liyu; Liu, Fencheng; Huang, Chunping
Abstract: The microstructure and corrosion behavior of oxide dispersion-strengthened (ODS) 304 stainless steel with Y2 O3 fabricated by hot isostatic pressing was compared with forged 304 stainless steel. The results show that microstructure of the 304 stainless steel was composed of austenite grains with size of 56 µm and a small amount of twins. Compared with 304 stainless steel, the grain size of ODS 304 stainless steel with Y2 O3 was much finer, which is about 6 µm. The corrosion current density of ODS 304 stainless steel was 1.13 μA/cm 2, which was lower than that of 304 stainless steel (1.63 μA/cm 2 ), that is decreased 30.6%. The polarization curves of two kinds of 304 stainless steel could be divided into three parts: activation region, passivation region and transpassive region. Compared with 304 stainless steel, the grain size distribution of ODS 304 stainless steel was relatively concentrated, the grain size was finer, which was beneficial to the corrosion resistance. Thus corrosion resistance of ODS 304 stainless steel was superior to the 304 stainless steel. Graphical Abstract: ga1